Prevalencia de Brucella Canis y Factores Asociados en Caninos Domésticos (canis familiaris) en el Barrio el Progreso de la Parroquia San Juan de Pastocalle. - Velasco López, Patricia Fernanda (2018)
Brucella is caused by brucellosis is a contagious infectious disease that affects the canines, causing a worldwide problem because the owners have no responsibility, and the necessary care with their pets. What this research determined is the prevalence of brucella canis and associated factors in domestic canines (canis familiaris) through the Rapid Test Kit in the El Progreso neighborhood of San Juan de Pastocalle parish where hematological samples were collected accompanied by a clinical record of 75 canines taking as a variable the age and separating by ranges of 0-12 months, 1-5 years and from 5 years and older the samples they are identified by numbering each of the patients, the owners applied a survey to relate the factors associated with brucella canis, these samples were transported to the Laboratory of the Technical University of Cotopaxi, where the rapid diagnostic test against brucella canis antibodies (Rapid Test Kit) was performed. As a result of the survey it was found that 93.33% of canines have wide space of which 14.60% have interaction with bovines sporadically, 100% of canines have food where 77.33% feed only on food from home, 85.33% of dogs have no veterinary control. Of the 75 dogs, the prevalence of 0% existed, thus determining that the associated factors do not influence to contract said disease. As a final result the owners were made aware of the responsible ownership of the pets and in this way avoid the spread of zoonoses diseases.